An innovative carbon template-induced approach to a graphene-like MnO2 nanomesh with enhanced pseudocapacitance performance. Issue 20 (5th May 2017) - Wang, Ziya; Wang, Fengping
Abstract : We first propose a sacrificial carbon template-induced method to generate a graphene-like MnO2 nanomesh with excellent electrochemical performances. Abstract : Exfoliated two-dimensional layered materials have gained renewed interest in the application of energy storage and conversion. In particular for pseudocapacitive materials, the ultrathin structure can resolve the disadvantage of their low proton/ion conductivity. Compared with the generally used liquid exfoliation, we first present an ingenious approach to directly realize a self-assembled mono/few-layered MnO2 nanomesh architecture by a simple in situ redox reaction between KMnO4 solution and a sacrificial carbon template. Electron microscopy, X-ray diffraction and spectroscopy results strongly suggest that the interconnected MnO2 nanosheets are separated into the individual layers. The synthesized graphene-like MnO2 nanomesh electrode exhibits a substantially increased specific capacitance (516.7 F g −1 ) with excellent cycle stability and coulombic efficiency, which is among the highest reported values of a pure MnO2 electrode with similar loading mass and demonstrates the promising potential supercapacitor and battery applications.